Islamic banking business of conventional banks: transition from windows to Islamic subsidiaries - Ramadili Mohd, Shamsher Mohamad; Mahomed, Ziyaad; Mustaffa Kamil, Nazrol Kamil (Pearson Malaysia, 2017)
Globally, Islamic banking grew by a compound annual growth rate of 17.3 percent between 2009 and 2014. The estimated size of the industry at the end of 2014 was given at US$2.1 trillion. This total dollar value of assets held by the Islamic financial institutions is less than 2 percent of the conventional banking industry; nonetheless, this is a huge achievement, considering it started from a zero base in the 1970s (Ernst & Young, 2013). Through the rate of growth has declined in recent years, the industry has nevertheless managed to grow by more than 15 percent even during the 2009 global crisis, whereas the overall banking assets remained static and economic growth in almost all countries was negative.